PEDAGOGICAL IMPLICATIONS OF PHONOLOGICAL PROBLEMS FOR LOCAL LANGUAGE SPEAKERS OF EFL LEARNERS IN WEST NUSATENGGARA - Nur Ahmadi; Arafiq; Nurachman Hanafi; Atri Dewi Aziz (Journal of English Education Forum (JEEF), 2023)
Learning English is so challenging especially to native speakers whose language sounds inventories are different from English. It will have been worst when learners are not aware of their problems. This article aims at formulating pedagogical implications of the phonological problems faced by the EFL learners in pronouncing standard English. The data in this research were obtained from the pronunciation test towards 30 EFL learners, 10 from each local language background (Sasak, Sumbawan, and Bimanese). The explanation begins with describing the pronunciation problems faced by the EFL Learners during the process of acquiring English and then followed with presenting the pedagogical implications that the learners can do to cope with the problems. The first pedagogical implication is the pronunciation training of changing voiceless bilabial stop [p] to make voiced and voiceless labiodental fricative [v] and [f] of English. The second is the pronunciation training of changing voiced and voiceless dental stops [D] and [T] to make voiced and voiceless alveolar stops [d] and [t], and the third is the pronunciation training of changing front middle sound [E] to central middle sound [ə] and [ɛ]. These pedagogical implications must be under a systematic and intensive training requiring the students’ awareness.